Patient background and prognosis of chronic pulmonary aspergillosis in fibrosing interstitial lung disease. Issue 32 (12th August 2022) - Yamakawa, Hideaki; Nishizawa, Tomotaka; Ohta, Hiroki; Tsukahara, Yuta; Nakamura, Tomohiko; Sato, Shintaro; Kawabe, Rie; Oba, Tomohiro; Akasaka, Keiichi; Amano, Masako; Kuwano, Kazuyoshi; Sasaki, Hiroki; et al.
Abstract : Several previous reports have shown interstitial lung disease (ILD) to be a predictor of poor prognosis in patients with chronic pulmonary aspergillosis (CPA). However, there is a lack of clarity regarding patient background and the prognostic factors in CPA associated with ILD (CPA-ILD). Therefore, we assessed these points to obtain valuable information for clinical practice. We retrospectively surveyed and collected data from 459 patients who had serum examination for anti- Aspergillus antibody. Of these patients, we extracted and investigated CPA-ILD patients. We ultimately analyzed 32 CPA-ILD patients. Patient background factors more frequently showed the patients to be older (mean: 74.9 years), male (75.0%), and to have a smoking history (71.9%). Median survival time from the diagnosis of ILD was 76.0 months, whereas that from the diagnosis of CPA-ILD was 25.5 months. No significant differences in survival were found in regard to each ILD pattern and the presence of idiopathic pulmonary fibrosis. A higher level of C-reactive protein was a significant predictor of mortality by Cox regression analysis. CPA complicating ILD is associated with poor prognosis. ILD patients with older age, male sex, and smoking history should be aware of the potential for the development of CPA in ILD. If such patients have elevated markers of inflammation, prompt induction of antifungal treatment may improve their prognosis. Clinicians should be aware of which complications of CPA may lead to a poor prognosis for any ILD not just those limited to idiopathic pulmonary fibrosis or usual interstitial pneumonia pattern.